The integrative action of the autonomic nervous system - Jänig, Wilfrid (Cambridge : Cambridge university press, 2008)
Foreword; Introduction; Part I. The Autonomic Nervous System: Functional Anatomy and Visceral Afferents: 1. Functional anatomy of the peripheral autonomic system; 2. Visceral afferent neurons and autonomic regulations; Part II. Functional Organisation of the Peripheral Autonomic Nervous System: 3. The final autonomic pathway and its analysis; 4. The peripheral sympathetic and parasympathetic pathways; 5. The enteric nervous system; Part III. Transmission of Signals in the Peripheral Autonomic Nervous System: 6. Impulse transmission through autonomic ganglia; 7. Mechanisms of neuroeffector transmission; Part IV. Central Representation of the Autonomic Nervous System: 8. Anatomy of central autonomic systems; 9. Spinal autonomic systems; 10. Regulation of organ systems by the lower brain stem; 11. Integration of homeostatic regulations in upper brain stem and limbic-hypothalamic centres: a summary.
boek